Análisis de la variación de la tasa de desempleo y su incidencia en las condiciones de vida en Ecuador. Periodo 2013 – 2017 - Gómez Alejandro, Xavier Emilio (2019)
In recent years, Ecuador has experienced evident labor instability that is reflected economically, both in the macroeconomic indicators as well as in the living conditions of the population residing in the country. The objective of the research is to analyze the variation of the unemployment rate and its impact on living conditions in Ecuador. Period 2013 - 2017. The methodology applied is exploratory with a mixed approach, and the techniques used were statistics from the Ecuadorian Institute of Statistics and Census and the Central Bank of Ecuador, and the interview with Econ. Alberto Dahik, which has as main results that the rates of national, urban and rural unemployment have not had a significant increase among themselves between the years of study, but did show an increase in 2015 but that later decreased. The city that has mostly felt the impact of unemployment, is the city of Quito since in 2013 it had a rate of 4.0% and in 2017 it grew to 9.40%, that is, it went up 5.4 p.p. Underemployment is one of the indicators that increased the most in recent years, passing in December 2013 from 11.64% to 19.8% in December 2017……….